Subordinação versus autonomia: duas faces do movimento sindical bancário cearense (1955-1964) - Menezes, Maria Zefisa Nogueira Soares (1984)
The proposition of autonomous syndicalism put forth during the fifties and sixties focuses on the independence and self management of brazilian trade unions in relation to the State. This paper analyses the actions of the Bank Workers Trade Union with respect to both political and economic demands through 1955-1964. Also in tries to reconstruct the search for autonomy through a critical examination of thade union practices during that period, emphasizing the limits to action when paradoxically at certain points, the trade unionists were supporting government reforms although they infact wanted to be independente from the State. The great strength of the bank workers to make economic demands, the increasing level of their political involvement revealed through participation in general political movements supported by CGT (General Confederation of Workers) and other civil segments of society; their participation in the fight for a strong and united Trade Union Movement were the signs of the search for autonomy that we were able to identify in the analysis, especially in the period beginning in 1959 when the nationalists took over the leadership of the Bank Workers Trade Union, defeating the conservatives. The enfoced links of trade unionism with the program of reforms proposed by the government represented one of the bounds on such autonomy as it demonstrated the lack of a well defined plan capable of transforming trade unionism into and independent entity. The plan for autonomous syndicalism headed by the nationlists both at the national and local level was characterised by ambiguity. It started from the premise that the autonomy of the working class was equivalent to the autonomy of the nation and that both would be attained by state reforms with the state itself becoming the generator of nationalist ideology and the national pact.